The evolution and construction of Shan-shui cities: evidence from the ancient city of Hangzhou from the sixth to the twenty-first century via geographical information systems and space syntax - Yue Huang; Yuhao Huang; Yile Chen; Yile Chen; Junxin Song; Shuai Yang; Lu Huang; Liang Zheng; Liang Zheng; Yike Gao (Frontiers in Earth Science)
The “Shanshui City” is an ideal living model that has emerged recently. The spirit and concept of traditional Chinese mountain and water culture run through it, reflecting the continuity of the historical culture of harmony between humanity and nature. This study takes the ancient city of Hangzhou as a representative case. Through the translation of old maps, combined with space syntax analysis and historical satellite image analysis, this study discusses the evolution of the urban form in four periods of the ancient city of Hangzhou: the Sui Dynasty to Five Dynasties and Ten Kingdoms Period (581–979), the Song Dynasty to Ming Dynasty (960–1644), the Qing Dynasty to the Republic of China (1644–1949), and since the founding of the People’s Republic of China (1949 to present). This study reveals the following: 1) The integration of the ancient city of Hangzhou evolved from local centralization in the Sui and Tang Dynasties to spatial expansion and improved integration in the Southern Song Dynasty, followed by differentiation and weakening from the Qing Dynasty to the Republic of China and, finally, to comprehensive optimization and balance in the modern era. 2) The evolution of the morphological understanding of the ancient city of Hangzhou reflects its adaptive adjustment to social needs, natural conditions, and functional optimization in different historical periods. From the compact concentration in the Sui and Tang Dynasties to the diversified integration in the Southern Song Dynasty and then to the spatial fragmentation and optimization reconstruction in modern times, the evolution of spatial morphology in different periods reflects the interaction between the historical process and planning wisdom. 3) From the perspective of historical land function changes, the architectural functional zoning of the ancient city of Hangzhou has evolved over time, showing a trend from simple to complex and from single-to multi-function areas, reflecting the different development needs and trends of the city in terms of defense, administration, residence, commerce, and other aspects. 4) Overall, the ancient city of Hangzhou has experienced a dynamic process of building city walls, demolishing city walls, and integrating the city into the landscape, fully demonstrating the concept of a landscape city.